Stability of DNA thymine hydrates. - Ganguly, T (1991)
Pyrimidine hydrates are products of ultraviolet irradiation of DNA. We have already demonstrated the formation of both cis-thymine hydrate and trans-thymine hydrate (6-hydroxy-5,6-dihydrothymine) in irradiated poly(dA-dT):poly(dA-dT). These are released from DNA as free bases by bacterial or human glycosylases. Thymine hydrate stabilities were studied in irradiated DNA substrates using purified E. coli endonuclease III as a reagent for their removal. After irradiation, substrate poly(dA-dT):poly(dA-dT), radiolabeled in thymine, was incubated at 50, 60, 70 or 80 degrees C, cooled, and then reacted with the enzyme under standard conditions. Thymine hydrates were assayed by enzymic release of labeled material into the ethanol-soluble fraction. Their identities were confirmed by high performance liquid chromatography. The decay of thymine hydrates in heated DNA followed first-order kinetics with a k = 2.8 x 10(-5)/sec at 80 degrees C. These hydrates were also detected in lesser quantities in the unirradiated, control substrate. Extrapolation from an Arrhenius plot yields an estimated half-life of 33.3 hours at 37 degrees C for DNA thymine hydrates. Such stability, together with their formation in unirradiated DNA, suggest thymine hydrates to be formed under physiological conditions and to be sufficiently stable in DNA to be potentially genotoxic. This necessitates their constant removal from DNA by the excision-repair system.